Pengaruh Stres Kerja, Beban Kerja, terhadap kepuasan Kerja (studi pada medical representatif di Kota Kudus) - Dhania, Dhini Rama (Universitas Muria Kudus, 2010)
With the growth of world trade in products where competition is accompanied by increasingly stringent targets are so high from the company to its marketing, as well as the marketing of drug company called Medical Representative is charged with a high enough target. Therefore this study aims to determine Workload Influence on Job Stress, Job Stress and Effect on Medical Representative Job Satisfaction in Kudus. From the results of hypothesis test showed that the adjusted R2 of -, 025 indicates that the effect of workload on job stress at 2.5%. With a very small effect, may imply that no form of workload influence on work stress. while for the Effect of Work Stress on Job Satisfaction gained 0,033 Adjusted R2 results show an effect of work stress on job satisfaction by 3.3%, With very little effect, may imply that no form of the effect of job stress on job satisfaction.